EFFECT OF TEMPERATURE, USE OF QUALITY THE QUAIL AND OCTOPUS WASTE IN DIGESTIVE TANK ON GAS BIO PERFORMANCE - Junus, Mochammad; Jaya, Firman; Ustadi; Kurniawan, Margomulyo Putra; Romadhon, Yoga Arif (International Journal of Research -GRANTHAALAYAH, 2021)
The aim of research to determine the effect of temperature and the use of livestock waste quail (LTP) and waste octopus (LG) in a digester tank is made of plastic curigen to the performance of gas bio production and nutrient content of sludge that is generated. The materials used are LTP and LG. The research method used 1) Randomized Block Design with 2 factors and 2) Completely Randomized Design with 6 treatments and 4 replications. The first factor is the waste with 6 treatments are P0: 100% LTP, P1: sludge 90% and 10% LTP LG, P2: sludge 80% LTP, and 20% of LG, P3: s ludge 70% LTP, and 30 LG, P4: LTP and 20% LG, P5: sludge 50% LTP and 50% LG. The second factor with lamps, namely P01: without lamps, P02: use 1 lamp, P03: use 2 lamps. Furthermore, LTP and LG are diluted with water until they reach 7% dry matter and stored in a digestion tank (made of 24 plastic jerry cans with a volume of 25 liters ). The analysis showed that the effects of temperature, the use of LTP and LG have influence which is not significantly different (P > 0.0 1 ) against the pressure, the volume of gas bioand H 2 S. Apart from that, it was also very significant (P <0.01) on the total N content, P elements and K elements, but the highest average total N and K element content was obtained in P0 sludge with a percentage of 100% LTP concentration. The conclusion of this study is that the effect of temperature, LTP, and LG affects the increase in gas bio production but not significantly different and the treatment of LTP and LG affects the increase in nutrient content.